Long-Term Outcomes and Prognosticators of Pediatric Primary Dilated Cardiomyopathy in an Asian Cohort - Wang, Po-Yuan; Tseng, Wei-Chieh; Fu, Chun-Min; Wu, Mei-Hwan; Wang, Jou-Kou; Chen, Yih-Sharng; Chou, Nai-Kuan; Wang, Shoei-Shen; Chiu, Shuenn-Nan; Lin, Ming-Tai; Lu, Chun-Wei; Chen, Chun-An (Frontiers in Pediatrics, 2021)
Background Dilated cardiomyopathy (DCM) is the most common childhood cardiomyopathy. The epidemiological profiles and prognosticators of clinical outcomes in Asian populations are not well elucidated. Methods Data of 104 children aged <18 years with a diagnosis of primary DCM from January 1990 to December 2019 in our institutional database were retrospectively investigated. Relevant demographic, echocardiographic, and clinical variables were recorded for analysis. A P value of <.05 was considered statistically significant. Results The median age at diagnosis was 1.4 years (interquartile range = 0.3-9.1 years), and 52.9% were males. During a median follow-up duration of 4.8 years, 48 patients (46.2%) were placed on the transplantation waitlist, and 52.1% of them eventually received heart transplants. An exceptionally high overall waitlist mortality rate was noted (27.1%), which was even higher (43.5%) if the diagnostic age was <3 years. The 1-, 5-, and 10-year transplant-free and overall survival were 61.1%, 48.0%, and 42.8% and 80.6%, 71.9%, and 67.3%, respectively. Age at diagnosis >3 years and severe mitral regurgitation at initial diagnosis were independent risk factors for death or transplantation (hazard ratios = 2.93 and 3.31, respectively; for both, P < .001). In total, 11 patients (10.6%) experienced ventricular function recovery after a median follow-up of 2.5 (interquartile range = 1.65-5) years. Younger age at diagnosis was associated a higher probability of ventricular function recovery. Conclusions Despite donor shortage for heart transplantation and subsequently high waitlist mortality, our data from an Asian cohort indicated that overall long-term survival was comparable with that noted in reports from Western populations. Although younger patients had exceptionally higher waitlist mortality, lower diagnostic age was associated with better long-term survival and higher likelihood of ventricular function recovery.